2019
DOI: 10.3892/ijo.2019.4945
|View full text |Cite
|
Sign up to set email alerts
|

Ophiopogonin D' induces RIPK1‑dependent necroptosis in androgen‑dependent LNCaP prostate cancer cells

Abstract: Ophiopogonin D' (OPD') is a natural compound extracted from Ophiopogon japonicus, which is a plant used in traditional Chinese medicine. Our previous study has indicated that OPD' exhibits antitumor activity against androgen-independent prostate cancer (PCa), but the effects and the underlying molecular mechanism of action of OPD' in androgen-dependent PCa were unclear. In the present study, OPD' induced significant necroptosis in androgen-dependent LNCaP cancer cells by activating receptor-interacting serine/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…IFN-γ can also induce a form of necrotic death, known as necroptosis, that involves serine–threonine kinase RIP1 ( 62 ). However, in most cancer cells, including prostate cancer cell lines PC3 and LNCaP, RIP1 is suppressed by caspase 8 ( 63 ) ( 64 ). Therefore it is more likely that the increased cell death we are seeing is through apoptosis mediated by both upregulated IFN-γ and perforin.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-γ can also induce a form of necrotic death, known as necroptosis, that involves serine–threonine kinase RIP1 ( 62 ). However, in most cancer cells, including prostate cancer cell lines PC3 and LNCaP, RIP1 is suppressed by caspase 8 ( 63 ) ( 64 ). Therefore it is more likely that the increased cell death we are seeing is through apoptosis mediated by both upregulated IFN-γ and perforin.…”
Section: Discussionmentioning
confidence: 99%
“… 2 79 Fas/FasL is well-known to induce RIPK-MLKL-mediated necroptosis as well as caspase-dependent apoptosis. 80 81 82 Milhas et al 83 have shown that D609 treatment enhances ceramide increase, leading caspase-independent cell death in response to FasL under zVAD-fmk-mediated inhibition of caspases in Jurkat cells. However, as the authors did not demonstrate the involvement of RIPK and MLKL activation, it was unclear whether this was necroptosis or not.…”
Section: Signal Transduction Is Regulated By Sms-mediated Ceramide/smmentioning
confidence: 99%
“…Paclitaxel, a complex diterpenoid compound extracted from the bark of Taxus brevifolia , has a spectrum and anti-cancer activity, especially for uterine cancer, ovarian cancer, and breast cancer ( Fader et al, 2018 ; Xiang et al, 2019 ). Ophiopogonin is an active ingredient extracted from Ophiopogonis Radix, including Diosgenin (Ophiopogonin B’, C’, and D’) and Ruscogenin (A, B, C, and D), that plays a role in delaying aging, improving learning and memory disorders, anti-cardio-cerebrovascular diseases, anti-tumor, anti-inflammatory, and immune regulation ( Wang et al, 2018 ; Lu Z. et al, 2020 ; Zhu et al, 2020 ). In the mouse model of middle cerebral artery occlusion (MCAO), Guan et al (2013) found that Ruscogenin protects against ischemic brain injury by inhibiting the NF-κB mediated inflammatory pathway.…”
Section: Introductionmentioning
confidence: 99%